The Meaning of Na’l in QS. Tāhā [20]: 12 (Semiotic Analysis By Roland Barthes) - TAUFIQ, MUHAMMAD (Aqwal: Journal of Qur'an and Hadis Studies, 2025)
Background and Objectives: This article examine the meaning of na’l (sandals) in the story of Prophet Moses as recorded in QS. Tāhā [20]: 12. Although na’l is often viewed as a profane object, it indicates a deep and significant meaning. This study assumes that the meaning of na’l is not limited to its literal dimension, but encompasses a broader and more universal meaning. Methodology: This study uses qualitative methods with a literature reviwe. To uncover these layers of meaning, Roland Barthes' semiotic approach is used, which consists of two levels of analysis, namely linguistic and mythological. This approach was chosen based on its ability to reveal new meanings in understanding ideology, culture, and social constructs. Main Results: The term na'l is not merely understood as a physical object in the form of footwear, but has been transformed into a symbol of all forms of obstacles, both physical and spiritual. Therefore, the interpretation of this verse contains a message for humans to remove all obstacles that prevent them from facing Allah. Main Results: The term na'l is not merely understood as a physical object in the form of footwear, but has been transformed into a symbol of all forms of obstacles, both physical and spiritual. Therefore, the interpretation of this verse contains a message for humans to remove all obstacles that prevent them from facing Allah. Conclusions: The semiotic approach emphasizes the importance of reading the Qur’an by paying attention to the symbolic context and the hidden meaning structure behind the text.